Multi-Omics Meta-Analysis Provides Insights into Reversible Phosphorylation During Arabidopsis Skotomorphogenesis - Gitman, Iván Federico Berco (2025)
We developed a pipeline to standardize and integrate publicly available transcriptomic,proteomic, and phosphoproteomic datasets from Arabidopsis thaliana etiolatedseedlings. The pipeline is broadly adaptable, as its database schema and processingscripts can be applied to datasets from any organism or experimental condition. Weapplied it to etiolated seedlings to uncover protein kinases and protein phosphatasesrelevant to early skotomorphogenic development, a stage in which seedlings growunderground and rely on precisely regulated signaling networks to ensure survival andsuccessful emergence. This multi-omics approach revealed a comprehensive landscapeof protein expression at this developmental stage; however, we observed widespreaddiscrepancies between transcript and protein abundance, pointing to post-transcriptionaland/or post-translational regulation. This cross-study minimizes experimental bias andallows the detection of phosphorylation events that may have been overlooked in singleconditionstudies. A search of kinase specific motifs revealed that RxxS motifs weresignificantly enriched among phosphorylated peptides in protein phosphatases andmicrotubule-associated proteins, suggesting regulation by calcium dependent proteinkinases (CPKs). CPK3 and CPK9 were identified as the most relevant isoforms in theproteome and phosphokinome, supporting their central role in skotomorphogenesis. Ourresults underscore the importance of phosphorylation-mediated signaling incoordinating early seedling development and provide a resource for dissectingregulatory networks and candidate genes involved in skotomorphogenesis.